The Microstructure of a Lexicographical Resource of Spoken German: Meanings and Functions of the Lemma eben - Christine Möhrs; Sarah Torres Cajo (Rasprave Instituta za Hrvatski Jezik i Jezikoslovlje, 2020)
This paper presents the corpus-based lexicographical prototype that was developed within the framework of the project Lexik des gesprochenen Deutsch (=LeGeDe) as a thirdparty funded project. Research results regarding the information offered in dictionaries have shown that there is a necessity for information on spoken lexis and its interactional functions. The resulting LeGeDe-prototype is based on these needs and desiderata and is thus an innovative example for the adequate representation of spoken language in online dictionaries. It is available online since September 2019 (https://www.owid.de/legede/). In the following sections, after first focusing on the presentation of the project’s goals, the data basis, the intended end user, and the applied methods, we will illustrate the microstructure of the prototype and the information provided in a dictionary entry based on the lemma eben. Finally, we will summarize innovative aspects that are important for the implementation of such a resource.